Concentration dependent morphology and composition of n-alcohol modified cetyltrimethylammonium bromide micelles. (14th November 2018) - Schmutzler, Tilo; Schindler, Torben; Goetz, Klaus; Appavou, Marie-Sousai; Lindner, Peter; Prevost, Sylvain; Unruh, Tobias
Abstract: Cetyltrimethylammonium bromide (CTAB) is one of the most commonly used surfactants in nanoparticle synthesis and stabilization. Usually, CTAB is used in high concentrations besides co-surfactants leading to well defined products but the complex mesoscopic CTAB structures stay mostly unknown. N -alcohols for instance are widely used co-surfactants which modify the properties of native CTAB dispersions. In this paper we report about a detailed structure analysis of n -alcohol modified CTAB micelles. In particular, n -pentanol and n -hexanol exhibit a significantly different influence on the size, shape and composition of CTAB micelles. Using a combination of small-angle x-ray spectroscopy (SAXS) and neutron scattering spectroscopy (SANS), we applied a method for a complete structural characterization of such micelles. The incorporation of n -pentanol into CTAB micelles generally does not influence the morphology but enhances the number of micelles due to the volume of the added alcohol. N -hexanol, however, leads to an elongation of the micelles as a function of its concentration. It was found by extended contrast variation measurements that this difference is caused by a different distribution of the alcohols between the micellar core and shell. N -pentanol molecules are generally located at the core–shell interface of the CTAB micelles with not only the head group but also two additional methylene bridging groups located in the micellar shell. This leads to an increase of its effective head group volume. In comparison, in n -hexanol modified micelles the whole alkyl chain is located within the micellar core. The detailed structure for n -alcohol modified CTAB micelles is described herein for the first time. The knowledge of the structural details found is indispensable for an in-depth understanding of CTAB– n -alcohol–water interfaces in general which is relevant for the synthesis of many functional nanostructures like mesoporous silica and gold or silver nanoparticles.